Pure math 2 : 0 = 1!

Consider the following proof.

0=(11)+(11)+(11)++(11)1    0=1+(1+1)+(1+1)++(1+1)2    0=1+0+0++03    0=140 = (1-1) + (1-1) + (1-1) + \ldots + (1-1) \rightarrow \fbox{1}\\ \implies 0 = 1 + (-1+1) + (-1+1) + \ldots + (-1+1) \rightarrow \fbox{2}\\ \implies 0 = 1 + 0 + 0 + \ldots + 0 \rightarrow \fbox{3} \\ \implies 0 = 1 \rightarrow \fbox{4}

The above is a Mathematical fallacy.

If you know that the proof is wrong, find which step is being wrong.

×

Problem Loading...

Note Loading...

Set Loading...